Big Little Spells: Witchlore # 2 - Beck, Hazel (Toronto, Ontario, Canada : Graydon House, 2023)
Returning to her coven ten years after being stripped of her magic and banished, Rebekah faces a death sentence as a danger to witchkind in the second novel of the series following Small Town, Big Magic.
Is her magic a threat to witchkind$1! =(Bor is she simply powerful enough to save the world? Rebekah Wilde was eighteen when she left St. Cyprian, officially stripped of her magic and banished from her home. Ten years later, she$1 (Bs forced to return to face the Joywood Coven, who preside over not just her hometown but the whole magical world. Rebekah is happy to reunite with her sister, and with her friends, but the implications of her return are darker and more dangerous than they could have imagined. The Joywood are determined to prove Rebekah and her friends are a danger to witchkind, and her group faces an impending death sentence if they can$1 (Bt prove otherwise. Rebekah must seek help from the only one who knows how to stop the Joywood-the ruthless immortal Nicholas Frost. Years ago, he was her secret tutor in magic, and her secret impossible crush. But the icy immortal is as remote and arrogant as ever, and if he feels anything for Rebekah-or witchkind-it$1 (Bs impossible to tell.s
new book 2023 fall.
Keywords: Witches -- Fiction; Magic -- Fiction; Small cities -- Fiction; Homecoming -- Fiction; Sisters -- Fiction; Man-woman relationships -- Fiction; Witch fiction; Paranormal fiction; Novels; Romance fiction; Fantasy fiction